Experimental investigation on combustion behaviour, performance and emission of fusel oil-gasoline blends using turbocharged SI engine - sm, rosdi; R. Mamat; M.H.M. Yassin; T. F. Yusaf; F. Khoirunnisa (Journal of Mechanical Engineering and Sciences, 2022)
Because of rising energy demand and pollution concerns in the transportation and industrial sectors, alternative fuel development is critical. The fusel oil, which is a by-product of ethanol distillation molasses, is receiving a lot of interest. The combustion characteristics, performance, and emissions of a 1.8L turbocharged four-cylinder, port injection, spark-ignition engine will be used to compare fusel oil blends with gasoline in this study. The experiment was carried out at a constant engine speed of 2000 rpm with a throttle load of 10-40%. Four samples with various ratios of gasoline combined with fusel oil were tested (100% gasoline, 10%, 20%, and 30% are referred to as F0, F10, F20, and F30 respectively). As a result, compared to gasoline, fusel oil blends increase Brake Specific Fuel Consumption (BSFC) by 5-22%. In comparison to gasoline, the combustion behaviour of in-cylinder pressure, Rate of Heat Release (ROHR), Rate Of Pressure Rise (ROPR), and Mass Fraction Burn (MFB) shows an early 2-3 Degree Crank Angle (CAD). Due to differences in attributes and oxygen content, the Brake Thermal Efficiency (BTE) of combustion utilising fusel oil blends suffers a modest drop of 13-16%. When compared to gasoline, fusel oil blends emit 3-4% less hydrocarbon (HC), 7.5-24.5% less carbon monoxide (CO), and 18-36% less nitrogen oxide (NOx). To summarise, fusel oil blends without water extraction blended with gasoline have a substantial impact on turbocharger engine functioning.